Missing link [videorecording (DVD)] - Butler, Chris, 1974-; Butler, Chris, 1974- (Twentieth Century Fox Home Entertainment, 2019)
The charismatic Sir Lionel Frost considers himself to be the world's foremost investigator of myths and monsters. Mr. Link only wants to find the missing branch of his sasquatch family, the yeti of Tibet, and hires Sir Frost to help him search. Unfortunately, Adelina Fortnight -- a fierce woman who has crossed paths with Sir Frost before -- holds the only map, and they are pursued by a villain hired by the Adventuring Society who would like Mr. Link's head as a trophy.